Cumulative effect of belief, effort - Ishak, Mohamed Mustafa (News Straits Times, 2015)
The late newspaper editor D. Everett wrote 'large streams from little fountains flow, tall oaks from little acorns grow..' all those years ago in 1790, but the beauty of such a truth is that it is self-evident.